Implementasi Undang-Undang Nomor 3 Tahun 2020 Terhadap Tata Kelola dan Kepastian Hukum Pertambangan Emas Skala Kecil dan Tradisional di Kabupaten Bone Bolango - Hidjun, Lion; Mato, Alvian; Uno, Ismail (Al-Mizan (e-Journal), 2025)
Artisanal and Small-Scale Gold Mining (ASGM) continues to take place outside the official licensing system and standardised management. This study aims to analyse the governance and legal certainty of small-scale mining based Law No. 3 of 2020 concerning Amendments to Law No. 4 of 2009 concerning Mineral and Coal Mining, and Government Regulation No. 96 of 2021 concerning the Implementation of Mineral and Coal Mining Business Activities, as well as to examine the gap between legal norms and their implementation at the regional level. This study uses a normative-empirical method utilising secondary data in the form of literature studies. The results show that the main problem with small-scale mining is not the absence of regulations, but rather the weak capacity of regional institutions, poor coordination between levels of government, the suboptimal designation of Small-Scale Mining Areas (WPR), and limited supervision and technical guidance. These conditions have led to the proliferation of small-scale gold mining without permits, high exposure to mercury in water and sediments, a decline in environmental quality, and increased occupational safety and health risks for miners. Thus, coordination and cooperation between the mining community and the government in these activities is necessary.